2020
DOI: 10.1002/brb3.1898
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of early systolic blood pressure variability after endovascular thrombectomy and intravenous thrombolysis in acute ischemic stroke: A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…BPV, reflecting the extent of BP fluctuations, has been regarded as a novel risk factor for worse outcome, brain oedema and HT after stroke 23–26. Previous studies suggested that increased BPV was associated with worse outcome in patients who had an AIS treated with recombinant tissue plasminogen activator (rt-PA) 23 26–28. Moreover, the finding that increased postprocedural BPV was associated with worse outcome has also been reported in studies of patients treated with MT 29 30.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…BPV, reflecting the extent of BP fluctuations, has been regarded as a novel risk factor for worse outcome, brain oedema and HT after stroke 23–26. Previous studies suggested that increased BPV was associated with worse outcome in patients who had an AIS treated with recombinant tissue plasminogen activator (rt-PA) 23 26–28. Moreover, the finding that increased postprocedural BPV was associated with worse outcome has also been reported in studies of patients treated with MT 29 30.…”
Section: Discussionmentioning
confidence: 92%
“…Accordingly, BP fluctuation may directly worsen the extent of injury to the ischaemic penumbra, leading to the growth of the infarct core, and hence worse functional outcome. 27 28 Another possible explanation might be that higher BPV may contribute to a greater disruption of blood brain barrier (BBB) and lead to exacerbation of reperfusion injury. 13 Previous research suggested that higher BPV might increase the permeability of the BBB and the risk of haemorrhage transformation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two meta-analysis described an association between the variability of the SBP and a poor clinical result 45 , 46 , but no association with the 90-day mortality 46 . Further meta-analyses confirmed a significant association of increased SBP after MT 47 or pre- and post-interventional 9 with a poor clinical result. In addition, increased post-interventional systolic and diastolic BP values were associated with increased mortality 9 .…”
Section: Discussionmentioning
confidence: 78%
“…Recently, neurologists propose that BP variability (BPV) may also play a role in affecting clinical outcome for AIS patients, in addition to the absolute BP level [ 6 ]. It is expected that the ischemic tissue would be more susceptible to blood pressure fluctuation given the impairment of cerebral autoregulation by stroke [ 7 ].…”
Section: Introductionmentioning
confidence: 99%